Oxford elementary learner's dictionary - "Crawley, Angela" (Oxford Universty Press, New York, 2002)
A practical first dictionary for learners of English. There are many examples and/or illustrations to show how words are used, notes on difficult words, dedicated pages to illustrate topics such as numbers, shapes etc. and information on pronunciation